Efficiency and Fairness in Islamic Banking Regulation: An Economic Analysis of Law Perspective - Rizki Aji Permana; Romadhon; Dede Kania (al-Afkar, Journal For Islamic Studies, 2026)
The Economic Analysis of Law (EAL) theory proposed by Richard A. Posner holds significant relevance in the regulation of Islamic banking, particularly in assessing the effectiveness and efficiency of regulations to achieve economic objectives. EAL emphasizes the importance of flexible and responsive regulations to market needs, as well as the integration of Sharia principles without hindering innovation. In the context of Islamic banking, regulations must adhere to Sharia principles such as the prohibition of riba and fairness in risk-sharing, while also promoting financial efficiency and stability. This study aims to analyze how EAL can assist in designing regulations that maximize economic benefits while ensuring social justice, in line with maqashid sharia. Using a qualitative and normative-analytical approach, this research compares the concepts of EAL with the principles of Islamic banking and identifies the challenges in aligning efficiency and justice in regulatory practice. The findings of this study suggest that the application of the Economic Analysis of Law (EAL) theory in the regulation of Islamic banking is crucial for achieving a balance between economic efficiency and social justice. While EAL focuses on optimizing resources for maximum economic benefit, in the context of Islamic banking, regulations must still consider Sharia principles such as the prohibition of riba and distributive justice. The main challenge lies in the need for regulations that are flexible and responsive to market dynamics, so they can integrate Islamic moral values with the need for efficiency. Therefore, well-designed regulations can support the sustainable and stable growth of Islamic banking, while meeting societal needs in accordance with maqashid sharia.